Peanut cultivar Botutatu yield affected by liming and harvest time - Antonia Vieira Rossetto, Claudia; Nakagawa, João; Antonio Rosolem, Ciro (Pesquisa Agropecuaria Brasileira, 1998)
A field experiment was carried out to study the effects of liming and time of harvesting on peanut cv. Botutatu (Arachis hypogaea L.) seed yield and yield components in the period of July, 1991 to February, 1992, in São Manuel, State of São Paulo. The soil was a Dark Red Latosol (Hapludult, sandy loam), and the experimental design was a subplot replicated four times in completely randomized blocks. Lime levels (0.0 and 1.75 t/ha) were applied in the plots, and the subplots were nine weekly harvests, starting at 87 days after planting (DAP). There was no effect of lime on hulls or seed yield and on peanut yield components. The germination of seeds in hulls was incresead at each harvest and was lower at lime presence. The highest yield was observed at 129 DAP.